Evaluation of age group swimmers: A in field proposal - Morouco, P.; Sacadura, J.; Amaro, N.; Matos, R. (The Open Sports Sciences Journal, 2010)
Swimming evaluation it`s the most appropriate procedure to analyze the development of a swimmer since age group swimming. The training control provides tools to prescribe intensities and volumes of training, but also assesses the improvement of each swimmer throughout that prescription. In the season 2007/2008 Leiria` Swimming Association had 419 swimmers competing by 13 Swimming Clubs. A selection process through 3 different stages was taken and evaluations were processed according to the swimmer development.